Tests of a novel re-centering damper with SMA rods and friction wedges. (1st June 2021) - Zhang, Shaoyuan; Hou, Hetao; Qu, Bing; Zhu, Yongjing; Li, Kefan; Fu, Xinrui
Highlights: The damper remained damage-free after multiple tests. The surface condition of the wedge mating interface affects the damper performance. A theoretical model was derived for the proposed damper. A computer model was developed and validated for the proposed damper. Abstract: This research focused on development of a new type of re-centering damper consisting of the Ni-Ti Shape Memory Alloy (SMA) rods and friction wedges. Compared with the other existing types of SMA-based dampers, the proposed damper offers an improved energy absorption capacity. In addition, strength and deformation capacity of the proposed damper can be conveniently adjusted if needed. To verify the perceived benefits of the damper, a series of tests were performed on an experimental specimen. It was found that the proposed damper can exhibit stable hysteretic energy dissipation response and reliable re-centering performance without developing any visible damage in the damper components. The test results also show that the damper is not sensitive to the different loading protocols imposed. Beyond the experimental work, a theoretical model for the proposed damper was established and validated by the test results. The theoretical model can be used to design the damper in the future. Furthermore, a three-dimensional computer model was developed for the tested damper. The computer model was found to be able to accurately replicate the nonlinear responses of the experimental specimen. The modelling approaches and assumptions adopted in the computer model can be used for future analysis and design.